2016
DOI: 10.1111/jcmm.12736
|View full text |Cite
|
Sign up to set email alerts
|

RUNX3 is down‐regulated in glioma by Myc‐regulated miR‐4295

Abstract: MicroRNAs are increasingly reported as tumour suppressors that regulate gene expression after transcription. Our results demonstrated that miR‐4295 is overexpression in glioma tissues and its level is significantly correlated with clinical stage. We also found that miR‐4295 inhibited the cell G0/G1 arrest and apoptosis leading to promoted cell proliferation and activity. The murine modelling study revealed that female nude mice injected with U87/anti‐miR‐4295 exhibit subcutaneous tumours in the right groin. Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 36 publications
2
12
0
Order By: Relevance
“…17 Propranolol has been used to treat high blood pressure, a number of types of irregular heart rate, thyrotoxicosis, and capillary hemangiomas. [20][21][22][23] However, the effect of miR-4295 has not been studied in IH. 2 MicroRNA-4295 (miR-4295) is one of the important miRNAs, which participates in mediating various biological processes, including cell proliferation, apoptosis, migration, and invasion.…”
Section: Introductionmentioning
confidence: 99%
“…17 Propranolol has been used to treat high blood pressure, a number of types of irregular heart rate, thyrotoxicosis, and capillary hemangiomas. [20][21][22][23] However, the effect of miR-4295 has not been studied in IH. 2 MicroRNA-4295 (miR-4295) is one of the important miRNAs, which participates in mediating various biological processes, including cell proliferation, apoptosis, migration, and invasion.…”
Section: Introductionmentioning
confidence: 99%
“…Intriguingly, we identified miR‐4295, an oncogenic miRNA, as a PTPN14‐targeting miRNA. Numerous studies have demonstrated that miR‐4295 expression is increased in various tumours, and it functions as a oncogenic miRNA that promotes the proliferation and invasion of tumour cells 45‐47 . In line with these reports, our study elucidated that miR‐4295 expression was increased in osteosarcoma tissues and cell lines.…”
Section: Discussionsupporting
confidence: 86%
“…Dysregulation of microRNAs is connected with various cancer sub-types, including GC ( 31 ). Overexpression of miR-4295 in glioma tissue was also reported, and its level was revealed to be associated with clinical stage ( 32 ). Furthermore, the present study identified that LRIG1 was a downstream target gene of miR-4295, and that LRIG1 was downregulated in GC cells.…”
Section: Discussionmentioning
confidence: 99%